The association of factor VIII activity levels with bleeding and quality of life in haemophilia a: findings from the European CHESS II study - Cheryl Jones; Yunchou Wu; Nana Kragh; Linda Bystrická; Amanda Wilson; Tom Burke (Orphanet Journal of Rare Diseases)
Abstract Background Haemophilia A is a rare disorder leading to excessive bleeding, resulting from a deficiency in circulating clotting factor VIII. While we know that raising factor VIII levels for extended periods of time would reduce the frequency of injections required and provide more consistent bleed protection, the relationship between factor activity levels (FALs), clinical outcomes, and health-related quality of life (HRQoL) for people with haemophilia A (PwHA) has not been well characterised. Objectives This study explored the relationship of FALs with annual bleeding rate (ABR) and HRQoL in PwHA. Methods This retrospective, cross-sectional study used data from the CHESS II study (2018–2020) including men aged ≥ 18 years with haemophilia A in Europe. Physicians provided patient characteristics and clinical outcomes from the medical records. Patients completed a questionnaire with HRQoL (EQ-5D) and socio-economic information. PwHA receiving on-demand treatment who had baseline factor VIII levels < 40 IU/dL and no inhibitors were included. Regression models explored FALs with ABR and HRQoL controlling for age, BMI, and presence of blood-borne viruses. Results A total of 403 PwHA were included (167 provided HRQoL responses). Mean age was 37 years. Mean baseline FAL was 7.0 IU/dL and mean ABR was 2.3 (SD, 2.64). A negative binomial model showed for every 1% increase in FVIII levels, ABR decreased by 3.9% (0.09 events; P < 0.001). A tobit model showed that every 1% increase in FVIII levels was associated with an increase of 0.0054 points in mean EQ-5D index score (P < 0.001). Conclusions This study offers tangible estimates of how higher FALs may relate to lower ABR and elevated HRQoL for PwHA.